(untitled) (Tempo e Argumento, 2013)
My paper describes some aspects of a research or rather a fellowship I conducted with a particular group of former Jewish children hidden in France during the occupation whosurvived the genocide and I met 60 years later. My purpose is based on my involvement with the Association for the memory convoy Y they have created and I will follow the various activities and conduct interviews with 16 participants. For over four years, I will follow the group: meetings, general meetings, commemoration trips in province, in Paris and Poland, exhibitions and various developments of the association. The group did’nt met in the name of their singular and painful experience of Jewish children hidden in France during the WW II, but on behalf of the memory of their parents deported in July 1942 and mostly murdered in Auschwitz. I wondered what was at stake in the dynamism of those contemporary meeting about traumas and disappearances of more than half a century, with the feeling that recovering road and possible mourning were authorized or legitimized by their research project, transmission aims and passion for archives.